2021
DOI: 10.1590/1676-0611-bn-2020-1164
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes of Proceratophrys ararype (Anura: Odontophrynidae), an endemic frog from the Araripe Plateau, northeastern Brazil

Abstract: Parasites are an important component of the global biomass, having significant roles in several regulatory mechanisms in the ecosystem. Parasitism is one of the most common ecological interactions on the planet. Studies have shown that the helminth fauna of only 8% of amphibian species in Brazil have been studied, and this percentage is lower for the Odontophrynidae family, with only four of the 50 species kown to occur in Brazil having been investigated. Here, we present the helminth fauna of Proceratophrys a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…This pattern was also found in other parasitological studies dealing with amphibians (e.g. Oliveira et al, 2019;Mascarenhas et al, 2021;Machado et al, 2022). It seems that this hypothesis might be more evidenced concerning a species pool with anuran species of different sizes (e.g.…”
Section: Journal Of Helminthologysupporting
confidence: 85%
See 4 more Smart Citations
“…This pattern was also found in other parasitological studies dealing with amphibians (e.g. Oliveira et al, 2019;Mascarenhas et al, 2021;Machado et al, 2022). It seems that this hypothesis might be more evidenced concerning a species pool with anuran species of different sizes (e.g.…”
Section: Journal Of Helminthologysupporting
confidence: 85%
“…In addition, we present 20 new host records (see table 2), reinforcing the importance of parasite checklists. Due to the increase in parasitological studies (Mascarenhas et al, 2021), it is quite common to find records of parasites not previously reported for host species (Aguiar et al, 2014;Silva et al, 2019). In the last decade, several studies on parasitism in Neotropical amphibians have been conducted (Madelaire et al, 2012;Aguiar et al, 2015;Chero et al, 2016;Amorim et al, 2019;Silva-Neta et al, 2020;Sani et al, 2021;Machado et al, 2022), with the nematode parasites Falcaustra mascula,…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations